PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN METODE LATIHAN BERSTRUKTUR UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Julianto; Gandung Sugita; Anggraini; I Nyoman Murdiana (Jurnal Elektronik Pendidikan Matematika Tadulako, 2021)
This research is motivated by students who experience problems in solving multiplication matrix problems and tend to be passive in the learning process. This research is a Classroom Action Research (CAR) which refers to the research design of Kemmis and Mc. Taggart namely (1) planning, (2) implementation of action (3) observation and (4) reflection. This study aims to describe the application of the cooperative learning model using structured training methods to improve student learning outcomes in class XI IPA 1 SMA Negeri 7 Palu. The subjects of this study were 32 students of class XI IPA 1, consisting of 15 male students and 18 female students. Of the 32 students, three students were selected as informants with high, medium and low skills. The results of the study the application of cooperative learning models with structured training methods can improve student learning outcomes in class XI IPA 1 SMA Negeri 7 Palu on Matrix Multiplication Material. The results of the final action test cycle I showed that of the 33 students who took the test, there were 11 students who achieved the learning objectives and 22 students did not achieve the learning objectives. The results of the final action test in cycle II showed that the student's score had increased from cycle I. Of the 33 students who took the test, there were 27 students who achieved the learning objectives and 6 students who did not achieve the learning objectives and 1 who did not take the test because they did not attend. From the results of the action test in cycle I and cycle II, it can be concluded that there was an increase in student learning outcomes from cycle I to cycle II